The United Nations: Between the Requirements of Establishment and the Challenges of Humanitarian Intervention: A Descriptive and Analytical Study in Light of International Law - Ramadan Masoud Khalifa (Journal of Scientific and Human Dimensions, 2026)
This study aims to examine the legal and political foundations of the United Nations, starting from its historical establishment following the failure of the League of Nations, up to its current role in maintaining international peace and security. The research focuses on the problematic issue of humanitarian intervention and the legal justifications for such actions under the UN Charter. Through a descriptive and analytical approach, the study evaluates the effectiveness of the UN’s mechanisms, analyzing the impact of the veto power held by the five permanent members of the Security Council. The findings highlight a structural imbalance within the organization that often leads to selective intervention and partiality in international conflicts, suggesting a need for institutional reform to ensure justice and equality among member states.